“A Sense of Seal” in Greenland: Kalaallit Seal Pluralities and Anti-Sealing Contentions - Graugaard, Naja (Études Inuit Studies, 2020)
This article questions the conceptual terms upon which Inuit hunting practices are deemed acceptable in current international seal regimes. Specifically, the article examines how Kalaallit–seal relations in Greenland unsettle Euro-American seal regimes. It argues that the current narratives of Inuit seal hunting as a “sustainable, subsistence” practice (e.g., European Commission 2016) risk coopting Indigenous worldviews to suit Western interpretations. While narratives of sustainability and subsistence may soothe European anti-sealing sentiments, they may not resonate with Inuit knowledges and practices. By engaging with fieldwork interviews with hunters in Greenland, this article suggests that Kalaallit ways of sensing, knowing, and engaging with seals reflect reciprocal, as well as complex, human–animal relations. Utilizing Métis/otipemisiw scholar Zoe Todd’s analytical framework of “fish pluralities” (2014), the article considers how seals may exist in Greenland in a “plurality of ways” that extend beyond a simple needs-based use of a natural resource